Ultrasound Accelerated Expedient and Eco-Friendly Synthesis of Aryl Sulfonates Using I2 As Catalyst At Ambient Conditions - Zhu, Sha; Wang, Bin-Bin; Tan, Mei-Chen; Qian, Xiaofu; Ying, Shengneng; Liu, Yang; Li, Cehua; Jin, Zheng; Jiang, Hongmei; Gui, Qing-Wen (Letters in Organic Chemistry, 2022)
Aryl sulfonates were developed by ssing an energy-saving and eco-friendly approach, through ultrasound-assisted coupling reaction of readily sodium sulfinates with N-hydroxyphthalimide, under metal-free and mild conditions within 10 min at room temperature.
Keywords: S-O bond forming